Some animals are more equal than others: wild animal welfare in the media - Feber, R; Raebel, E; D'Cruze, N; Macdonald, D; Baker, S (Oxford University Press, 2016)
The media can reflect social opinion and influence debate and policy. Wild vertebrate welfare issues are regularly reported in the media, but there has been no study of the type and frequency of their coverage. We compiled a list of potential wild vertebrate welfare issues in the UK, recording how often each issue was mentioned in the media during 2014. Lethal wildlife management issues were most frequently reported, while issues that received little coverage included marine debris, commercial fishing and pollution. Overall, the media tended more frequently to report welfare issues that involved intent to harm an animal, were illegal or occurred in the terrestrial environment. Insofar as media reporting may lead to improvements in the welfare of wild animals, greater effort may be required to provoke media interest in welfare issues that do not involve intent to harm, are legal or occur in marine environments